'Like jumping off a ledge into the water': A qualitative study of trauma‐focussed imaginal exposure for hearing voices. (19th November 2021) - Feary, Natalie; Brand, Rachel; Williams, Anne; Thomas, Neil
Abstract : Objective: There is growing evidence of a link between the experience of hearing voices and past traumatic events, and trauma‐focussed psychological interventions are being applied to hearing voices as an emerging treatment direction. To inform the ongoing development and implementation of this application, there is a need to understand clients' therapy experiences. Design: Qualitative study exploring the experience of people who received an intervention for voices linked to a previous traumatic event. Method: Ten participants experiencing voices with some connection to a previous traumatic event participated in individual semi‐structured interviews following six sessions of imaginal exposure, an exposure‐based trauma‐focussed intervention. Participant responses were analysed using thematic analysis. Results: Participants reported a range of benefits from the intervention, including improved mental health, reduction of distressing voice‐hearing experiences, and increased clarity of the traumatic event. The therapy was perceived as distinctly different to previous therapy experiences, and participants noted that therapy could be intense and challenging, yet helpful later. Participants also reported that outside circumstances impacted on their progress in therapy and their voice‐hearing experience. Conclusions: The findings suggest that exposure‐based trauma‐focussed therapies may be beneficial for people who hear trauma‐related voices. However, this intervention can be intense and clinicians and consumers need to consider the timing of delivery, and pay attention to internal and external resources that can increase participants' sense of safety. Practitioner points: Imaginal exposure may be an effective intervention for people who hear voices that they perceive to be associated with a past traumatic event. Positive changes associated with the intervention may be highly variable between individuals, and encompass changes in sense of self, changes to internal states, and changes to voice‐hearing experience. Imaginal exposure interventions may involve some temporary discomfort and symptom exacerbation, which may affect the acceptability of the intervention. This needs to be considered in both future research and clinical delivery.